The Stretta Procedure Versus Proton Pump Inhibitors and Laparoscopic Nissen Fundoplication in the Management of Gastroesophageal Reflux Disease: A Cost-Effectiveness Analysis - Dan Comay; Viviane Adam; Eduardo B da Silveira; Wendy Kennedy; Serge Mayrand; Alan N Barkun (Canadian Journal of Gastroenterology)
BACKGROUND: The Stretta procedure is an endoscopic therapy for gastroesophageal reflux disease.